Penerapan Show And Tell Method Untuk Meningkatkan Keterampilan Berbicara Siswa Di Kelas Rendah - Lala Sakinah; Andi Nurochmah; Din Azwar Uswatun (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2020)
This study aims to improve the process of implementing learning and improve students' speaking skills through the implementation of show and tell methods. This type of research is Classroom Action Research (CAR) using the Kemmis and Taggart designs through 2 cycles ranging from planning, implementation, observation, and reflection. The research participants were class II B students of Pintukisi Elementary School, Sukabumi City, with 34 students. Techniques for collecting data through interviews, observation, and documentation. The method of data analysis uses quantitative descriptive statistical analysis techniques. The indicator of success of this study is that at least 70% of the respondents reached the KKM score of 70. The results showed: (1) the process of implementing learning was good and a positive response was indicated by the average score of teacher performance in Cycle I: 60 II: 81 (Very good), Performance of students in cycle I: 62 (Good), and cycle II: 75 (good), (2) Show and tell methods can improve students' speaking skills. Improvement can be seen from the average value of students' speaking skills at pretest, which is 54 points to 68 points in the first cycle so that it increases by 14 points, with classical completeness of 32%. In the first cycle, it was 68 points to 81 points in the second cycle so that it increased by 13 points, with classical completeness of 91%. The achievement data above shows that show and tell methods are proven to be able to improve the quality of the learning process and students' speaking skills which are very significant.